Morphine reduced perceived anger from neutral and implicit emotional expressions. (May 2018) - Løseth, Guro E.; Eikemo, Marie; Isager, Peder; Holmgren, Jostein; Laeng, Bruno; Vindenes, Vigdis; Hjørnevik, Trine; Leknes, Siri
Highlights: Morphine reduced perception of anger in faces with neutral or implicit emotion expressions, known to invoke impressions of happiness and anger. Perception of anger in explicitly angry faces was not affected by morphine treatment, nor was perception of happiness across stimuli. The effect of morphine on anger perception was statistically unrelated to subjective drug effects, mood, autism trait and gender. Abstract: The μ-opioid system modulates responses to pain and psychosocial stress and mediates non-social and social reward. In humans, the μ-opioid agonist morphine can increase overt attention to the eye-region and visual exploration of faces with neutral expressions. However, little is known about how the human μ-opioid system influences sensitivity to and appraisal of subtle and explicit cues of social threats and reward. Here, we examined the effects of selective μ-opioid stimulation on perception of anger and happiness in faces with explicit, neutral or implicit emotion expressions. Sixty-three healthy adults (32 females) attended two sessions where they received either placebo or 10 mg per oral morphine in randomised order under double-blind conditions. Based on the known μ-opioid reduction of pain and discomfort, as well as reports suggesting that the non-specific partial agonist buprenorphine or the non-specific antagonist naltrexone affect appraisal of social emotional stimuli, we hypothesised that morphine would reduce threat sensitivity and enhance perception of happy facial expressions. While overall perception of others' happiness was unaffected by morphine treatment, morphine reduced perception of anger in stimuli with neutral and implicit expressions without affecting perception of explicit anger. This effect was statistically unrelated to gender, subjective drug effects, mood and autism trait measures. The finding that a low dose of μ-agonist reduced the propensity to perceive anger in photos with subtle facial expressions is consistent with the notion that μ-opioids mediate social confidence and reduce sensitivity to threat cues.